2017
DOI: 10.1186/s13024-017-0210-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of C5aR1 signaling delays microglial inflammatory polarization, favors clearance pathways and suppresses cognitive loss

Abstract: BackgroundPharmacologic inhibition of C5aR1, a receptor for the complement activation proinflammatory fragment, C5a, suppressed pathology and cognitive deficits in Alzheimer's disease (AD) mouse models. To validate that the effect of the antagonist was specifically via C5aR1 inhibition, mice lacking C5aR1 were generated and compared in behavior and pathology. In addition, since C5aR1 is primarily expressed on cells of the myeloid lineage, and only to a lesser extent on endothelial cells and neurons in brain, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
116
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(132 citation statements)
references
References 91 publications
15
116
1
Order By: Relevance
“…Furthermore, we identified markers which were exclusive to the C5AR1-expressing microglia (SLAMF1, FAS, MILR1, and LAIR1), but also generalised markers which were not (CD44 and BST2). This agrees with other reports which suggest that C5AR1 is needed for microglial polarisation to pro-inflammatory states, and that its knock-out improved outcomes in an Alzheimer's model (36). Furthermore, microglial heterogeneity has already been reported in Alzheimer's disease, light-damage models, and in response to LPS stimulation in vivo (8,13,32).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, we identified markers which were exclusive to the C5AR1-expressing microglia (SLAMF1, FAS, MILR1, and LAIR1), but also generalised markers which were not (CD44 and BST2). This agrees with other reports which suggest that C5AR1 is needed for microglial polarisation to pro-inflammatory states, and that its knock-out improved outcomes in an Alzheimer's model (36). Furthermore, microglial heterogeneity has already been reported in Alzheimer's disease, light-damage models, and in response to LPS stimulation in vivo (8,13,32).…”
Section: Discussionsupporting
confidence: 92%
“…Fu and colleagues have shown that APP/PS1 mice treated with the cytokine IL-33 present lower levels of pro-inflammatory gene expression (i.e., IL-1β , IL-6 , NLRP3 ) in association with reduced Aβ load, increased magnitude of long-term potentiation (LTP) at Schaffer collateral-CA1 synapses, and improved cognitive function [ 99 ]. Blockage of mediators of the complement cascade, including C1q [ 100 ], C3 [ 101 , 102 ], and C5a [ 103 ], also confers neuroprotective effects in mouse models of AD. Moreover, deficiency of IκB kinase β, which activates NF-κB, in microglia reduces inflammatory activation and Aβ load in the brain of TgCRND8-APP mice, effects which are associated with a reduction in cognitive deficits and preservation of synaptic structural proteins [ 104 ].…”
Section: The Complexity Of Pro- and Anti-inflammatory Timingmentioning
confidence: 99%
“…However, to be sure C5a acts via C5aR1 inhibition, C5aR1 deficient mice were generated, and compared to wild type mice plaque load and behavioral assessments such as novel object recognition (NOR), hpc dependent and independent versions and object location memory (OLM), hpc dependent. [ 27 ]…”
Section: Omplement S Ystem Inmentioning
confidence: 99%
“…As stated, to accomplish this, C5aR1 knockout mice were crossed to the Arctic AD mouse. Hernandez et al (2017) [ 27 ] found C5aR1 deficient mice did not show behavior deficits at 10 months, although amyloid plaque load was not altered. Of interest, there were no CCR2+ monocytes/macrophages near the plaques in the Arctic brain with or without C5aR1.…”
Section: Omplement S Ystem Inmentioning
confidence: 99%